Severe skin complications of varicella in previously healthy children in Iran: emerging concern - Hamed Tabasizadeh; Shima Mahmoudi; Mahmoud Khodabandeh; Hamid Eshaghi; Mohammad Reza Abdolsalehi; Maedeh Gooran; Hani Rostami Rad; Reihaneh Hosseinpour Sadeghi; Setareh Mamishi (BMC Infectious Diseases)
Abstract Background Varicella, commonly known as chickenpox, is typically considered a mild childhood illness but can lead to severe complications necessitating hospitalization. In Iran, the varicella-zoster vaccine is not currently included in the routine immunization schedule. This case series study aimed to characterize severe skin complications of varicella in children admitted to an Iranian referral hospital. Materials and methods This case series study reviewed 17 pediatric cases hospitalized for severe skin complications of varicella and demographics data, clinical presentation, and the outcomes were collected. Results Between December 2023 and March 2024, a total of 98 cases diagnosed with varicella were screened in our hospital, of which 17 cases (17.3%) presented with severe skin complications. Among 17 cases analyzed, 82.3% were males (n = 14) with a mean age of 6.9 ± 3.9 years. Severe skin complications of varicella manifested across diverse anatomical sites, with the chest and neck emerging as the most frequently affected areas. Cellulitis was a consistent finding across all cases, while abscess formation was noted in six instances. Particularly noteworthy was a case of necrotizing fasciitis localized to the thigh and leg region, underscoring the potential severity of varicella-related complications. Furthermore, we documented an instance of preseptal cellulitis linked to varicella zoster virus infection. Treatment involved local wound care, broad-spectrum antibiotics, and surgical intervention in six cases. Bacterial cultures identified Group A β-hemolytic Streptococcus in 35.3% of cases. Conclusion Our study highlights the spectrum of severe varicella-related skin complications and underscores the importance of prompt recognition and management to prevent morbidity and optimize outcomes. Further research and analysis of varicella epidemiology in Iran are essential to evaluate the benefits and feasibility of integrating the varicella-zoster vaccine into the national immunization program.